2010
DOI: 10.1111/j.1752-4571.2009.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific responses to landscape fragmentation: implications for management strategies

Abstract: Habitat fragmentation affects the integrity of many species, but little is known about species-specific sensitivity to fragmentation. Here, we compared the genetic structure of four freshwater fish species differing in their body size (Leuciscus cephalus; Leuciscus leuciscus; Gobio gobio and Phoxinus phoxinus) between a fragmented and a continuous landscape. We tested if, overall, fragmentation affected the genetic structure of these fish species, and if these species differed in their sensitivity to fragmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
128
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(143 citation statements)
references
References 83 publications
(216 reference statements)
13
128
2
Order By: Relevance
“…This surprising conclusion gives hope for the survival of pine martens and related mustelids in our human-dominated world, although ongoing urbanization may already have started to impact gene flow at a yet still undetectable level and may impact genetic diversity in the future. Besides, our results reinforce the statement of Blanchet et al (2009) that the effects of habitat fragmentation may strongly differ between (groups of) species, and should therefore be assessed separately for organisms with different life histories. While any potential negative impact of infrastructural works on wildlife connectivity is best avoided, detailed and landscape-scale information on multiple species would strongly aid managers to prioritize and optimize measures to mitigate the effects of fragmentation.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This surprising conclusion gives hope for the survival of pine martens and related mustelids in our human-dominated world, although ongoing urbanization may already have started to impact gene flow at a yet still undetectable level and may impact genetic diversity in the future. Besides, our results reinforce the statement of Blanchet et al (2009) that the effects of habitat fragmentation may strongly differ between (groups of) species, and should therefore be assessed separately for organisms with different life histories. While any potential negative impact of infrastructural works on wildlife connectivity is best avoided, detailed and landscape-scale information on multiple species would strongly aid managers to prioritize and optimize measures to mitigate the effects of fragmentation.…”
Section: Discussionsupporting
confidence: 74%
“…Yet, responses are variable among groups of species (Blanchet et al 2009). Many carnivorous mammals are disproportionately affected by habitat destruction, as they typically occur in low densities and thus require large areas to sustain a genetically viable population (Henle et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…KAM). Despite their small-scale, such structures can fragment river ecosystems and impede dispersal, leaving fish populations vulnerable to subsequent disturbance (Blanchet et al, 2010). While the analysis of fish presence verses barriers was not statistically significant, this result may, in part, be explained by the absence of fish at several burnt sites without barriers where naturally steep channel slopes may have otherwise restricted colonization.…”
Section: Discussioncontrasting
confidence: 42%
“…Host sampling was conducted by electric-fishing according to French legislation and prefectoral decrees from the Direction Départementale des Territoires at eight sampling sites which cover the whole distribution of dace in the river (see the electronic supplementary material, figure S1). We consider individuals from these sampling sites to belong to the same population, because we previously showed that genetic spatial structure in this river was weak (with a mean pairwise F ST ¼ 3.06% [30]). These eight sampling sites have been monitored at the end of June for each year from 2005 to 2011.…”
Section: (C) Field Sampling Protocolmentioning
confidence: 99%